The opposing effect of gamma irradiation on proton and sodium ion conduction in Na2Ti3O7 and its defective analog - Maluangnont, Tosapol; Chaithaweep, Kanokwan; Sangtawesin, Tanagorn; Vittayakorn, Naratip (My University, 2026)
It is known that γ-irradiation of Na2Ti3O7 induces Na + ion deintercalation, oxygen-vacancy formation, and proton/water incorporation, yielding the defective phase Na2- x H0.5 x Ti3O7-0.5 x (OH)0.5 x with multiple charge carriers. Although Na2Ti3O7 is a well-studied ion conductor, charge-transport details in its γ-irradiated analogs remain limited. Here, we report their AC conductivity and dielectric properties under a temperature cycle (RT→350 °C→RT). Proton conduction dominates at ambient temperature but diminishes upon heating. This produces a dehydration-driven increase of resistivity known as the apparent Positive Temperature Coefficient of Resistivity (PTCR) effect, consistent with the Heywang model recently applied to water-adsorbing ceramics. Proton conductivity increases with γ-irradiation dose up to 200 kGy, then decreases at 400 kGy due to excessive structural disorder. At high temperatures, Na+ ion conduction prevails and follows Arrhenius behavior, with activation energy decreasing with dose. This discrepancy might be understood considering that Na+ ion conduction is governed primarily by its concentration rather than mobility; excessive doses lower activation energy but deplete Na+ ions and decrease conductivity. Dielectric-loss fitting using Jonscher's universal dielectric response (UDR) indicates that proton-transport pathways are sensitive to thermal history, whereas Na+ ion conduction exhibits low-frequency dispersion (LFD) across all conditions.